Internalisasi Nilai-Nilai Islam dan Kearifan Lokal dalam Penguatan Kesadaran Lingkungan Siswa di MAN Batu Bara: Penelitian - Siti Lubis; Anri Naldi; Firmansyah Firmansyah; Cahaya Cahaya; Aqila Khairani (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
This study aimed to analyze the internalization of Islamic values and local wisdom in strengthening students’ environmental awareness at MAN Batu Bara as an effort to develop environmentally responsible character based on religiosity and local culture. This study employed a qualitative approach with a case study design. Data were collected through participatory observation, in-depth interviews with the headmaster, Islamic education teachers, student organization supervisors, and students, as well as documentation of environmental programs conducted in the madrasah. The data were analyzed using Miles and Huberman’s interactive analysis model, which consisted of data reduction, data display, and conclusion drawing. The results showed that the internalization of Islamic values had been implemented through religious habituation activities, reinforcement of Islamic teachings on khalifah fil ardh, the concept of thaharah, and the prohibition of israf, which had been integrated into classroom learning and extracurricular activities. Meanwhile, local wisdom in Batu Bara society had been utilized to shape students’ ecological behavior through the practices of mutual cooperation (gotong royong), environmental cleanliness culture, and responsible use of natural resources. The implementation of these value-based programs had significantly improved students’ environmental awareness, as indicated by positive behavioral changes, increased participation in greening activities, higher concern for cleanliness, and reduced plastic waste within the madrasah environment. This study concluded that the integration of Islamic values and local wisdom had effectively strengthened students’ environmental awareness in a sustainable manner.